2014
DOI: 10.1101/cshperspect.a021550
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis D Virus Coinfection and Superinfection

Abstract: HDV is a defective RNA pathogen requiring the simultaneous presence of HBV to complete its life cycle. Two major specific patterns of infection have been described: the coinfection with HDV and HBV of a susceptible, anti-HBs-negative individual, or the HDV superinfection of a chronic HBV carrier. Coinfection mostly leads to the eradication of both agents, whereas the majority of patients with HDV superinfection evolve to chronic HDV infection and hepatitis. Chronic HDV infection worsens the preexisting HBV-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 56 publications
2
103
0
Order By: Relevance
“…Hepatitis delta virus (HDV) is an RNA‐defective virus that requires the simultaneous presence of hepatitis B virus (HBV) to be infectious and fully express its pathogenicity and, therefore, hepatitis D infection always occurs in the presence of HBV . HDV infection can be acquired by patients already infected with HBV (superinfection) or through simultaneous infection by both HDV and HBV (coinfection) . Both superinfection and coinfection can initially have similar symptomatology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis delta virus (HDV) is an RNA‐defective virus that requires the simultaneous presence of hepatitis B virus (HBV) to be infectious and fully express its pathogenicity and, therefore, hepatitis D infection always occurs in the presence of HBV . HDV infection can be acquired by patients already infected with HBV (superinfection) or through simultaneous infection by both HDV and HBV (coinfection) . Both superinfection and coinfection can initially have similar symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of HDV/HBV‐coinfected patients is typically benign with acute self‐limited hepatitis and few cases of acute liver failure . In contrast, most HDV superinfections evolve to chronicity and can sometimes cause liver failure or significant worsening of underlying chronic hepatitis B . Several cohort studies in which chronic hepatitis delta patients were followed for a variable time period have analysed the cumulative rate of hepatic decompensation and liver‐related deaths .…”
Section: Introductionmentioning
confidence: 99%
“…In HDV, VCTE has not yet been validated and two recent studies evaluating noninvasive serum tests have demonstrated inadequate performance . Concerns exist on whether these noninvasive tests can be clinically useful in chronic HDV since HDV is associated with severe necroinflammation which may skew testing results . It remains unclear if noninvasive testing, especially VCTE, has any clinical value in chronic HDV and if the pre‐existing VCTE cut‐offs for HBV or HCV are applicable to HDV.…”
Section: Introductionmentioning
confidence: 99%
“…(8) In our patient population with chronic hepatitis B and delta, we recorded a steady decrease of thrombocyte counts over time, with 7,000/µL in 1.3 years and 17,000/µL in 2.8 years after diagnosing HDV infection. This information is derived from a patient population that already presented some degree of fibrosis at baseline, but notably only 21.1% of the patients presented cirrhosis.…”
Section: Discussion Discussionmentioning
confidence: 98%